The terms "Loci communes" and "Loci" in Melanchthon - Breen, Quirinus (Church history, 1947)
Philip Melanchthon was the author of the first book of Protestant theology, which he called Loci communes rerum theologicarum seu hypotyposes theologicae (Wittenberg, 1521). As a first it is worth some study, for firsts are likely to be models for later things of their kind. Moreover, while Melanchthon is by some considered to depart from early Protestant thought (cf. Philippism), Luther gave unqualified and almost extravagant praise to his young collaborator's first work. This justifies putting at least the 1521 edition in the fundamental canon of Protestantism. Finally, if suth is its importance Melanchthon's method deserves examination.